AKTIVITAS ANTIOKSIDAN HIDROLISAT PROTEIN MIOFIBRIL BELUT (Synbranchus bengalensis) YANG DIHIDROLISIS DENGAN ENZIM PAPAIN - Arlina Hidayati; Joko Santoso; Desniar (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
Protein hydrolysates contain bioactive peptides which have several function in order to maintain health and reduce the risk of disease. One of the functions of bioactive peptides is as an antioxidant. This study aims to characterize eel myofibril (Synbranchus bengalensis), determine the effect of papain enzyme ratio and hydrolysis time on eel myofibril protein hydrolysates, determine the antioxidant activity of eel myofibril hydrolysates by using DPPH and reducing power assay, and characterize the hydrolysate of myofibril proteins which have the best antioxidant activity. The results showed that eel myofibril protein contained moisture, fat, protein and ash of 85.91, 0.15, 0.14 and 12.78% respectively and contained the highest glutamic acid and lysine. Hydrolysates of eel myofibril proteins treated using various enzyme ratio and hydrolysis time had hydrolysates yields ranging from 3.53-9.68%, the value of hydrolysis degrees 5.20 - 16.193%, IC50 14.24 - 30.26 mg/mL for DPPH assay and absorbance 0.125 - 0.190 at a concentration of 5 mg/mL for reducing power assay. Hydrolysis eel myofibril protein using ratio papain 0.20:100 for 2 hours produced the highest antioxidant activities measuring by DPPH scavenging and reducing power iron. The hydrolysate had molecular weight approximately 19.51 kDa. Glutamic acid and lysine became the dominant amino acids of the hydrolysate. Keywords: antioxidant, hydrolysates, myofibril, Synbranchus bengalensis, papain